2007
DOI: 10.1021/tx600275d
|View full text |Cite
|
Sign up to set email alerts
|

DNA Adduct Formation in the Livers of Female Sprague−Dawley Rats Treated with Toremifene or α-Hydroxytoremifene

Abstract: Toremifene, an analogue of tamoxifen in which the ethyl side chain has been replaced with a 2-chloroethyl substituent, is used as a chemotherapeutic agent in postmenopausal women with advanced breast cancer. Toremifene is metabolized in a manner similar to that of tamoxifen, with alpha-hydroxytoremifene being a predominant metabolite in incubations in vitro. DNA adducts have been detected previously in liver DNA upon the administration of toremifene to rats; however, the identity of these adducts is unknown. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Nevertheless, endometrial cancer rates are increased in women taking tamoxifen [13] . The chlorine substitution in the structure of toremifene alters its metabolism such that DNA adducts are much less likely to form [13,[63][64][65][66] and a case-control study based on records of 38000 Finnish breast cancer patients appears to suggest that toremifene is considerably less frequently associated with endometrial cancer than is tamoxifen [OR 2.9; 95%CI: 0.3-3.9 vs 0.9; 95%CI: 0.3-3.9) [17] . However, a recent meta-analysis of studies involving a total of 7242 patients with early or advanced breast cancer found no difference in the number of endometrial cancers between patients treated with toremifene or tamoxifen, although the follow-up was relatively short in the majority of studies.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Nevertheless, endometrial cancer rates are increased in women taking tamoxifen [13] . The chlorine substitution in the structure of toremifene alters its metabolism such that DNA adducts are much less likely to form [13,[63][64][65][66] and a case-control study based on records of 38000 Finnish breast cancer patients appears to suggest that toremifene is considerably less frequently associated with endometrial cancer than is tamoxifen [OR 2.9; 95%CI: 0.3-3.9 vs 0.9; 95%CI: 0.3-3.9) [17] . However, a recent meta-analysis of studies involving a total of 7242 patients with early or advanced breast cancer found no difference in the number of endometrial cancers between patients treated with toremifene or tamoxifen, although the follow-up was relatively short in the majority of studies.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Toremifene is as effective as tamoxifen in the treatment of ER-positive breast cancer but with the potential of fewer genotoxic effects, since it does not produce DNA adducts in rat liver and human endometrium [113]. The mechanism for the reduced genotoxicity of toremifene can be explained as follows: Tamoxifen-DNA adducts are primarily formed via sulfonation of the α-hydroxylated tamoxifen metabolites, but the α-hydroxy metabolites of toremifene is poorly esterified or sulfonated, and even sulfonated α-hydroxy toremifene, α-sulfoxytoremifene, reacts poorly with DNA [114, 115]. However, there are some reports to show toremifene induces DNA damages and hepatocarcinogenesis in rats [116, 117].…”
Section: New Sermsmentioning
confidence: 99%
“…DNA adducts can be induced by a variety of endogenous or exogenous sources of chemical species, such as byproducts of lipid peroxidation, 1,2 chemotherapeutic drugs, 35 tobacco carcinogens, 68 and environmental contaminants. 9,10 If not repaired correctly or timely, these adducts may lead to myriads of alterations within the cell, including, but are not limited to, cell death, mutations in the genome, and aberrant cell cycle control.…”
Section: Introductionmentioning
confidence: 99%